[OP.4B.04] URINARY PROTEOMICS PREDICTS MORTALITY IN TYPE 2 DIABETES PATIENTS WITH MICROALBUMINURIA. (September 2017) - Currie, G.; Von Scholten, B.J.; Mary, S.; Siwy, J.; Mullen, W.; Rossing, P.; Delles, C.
Abstract : Objective: There is a continuous relationship between mortality and degree of diabetic nephropathy (DN) but neither estimated glomerular function (eGFR) nor albuminuria are precise early markers of renal function decline. The CKD273 urinary proteomic biomarker has shown promise as a tool for early detection of kidney disease, particularly DN. Here we study whether CKD273 predicts mortality in patients at early stage of DN. Design and method: Urine samples were obtained from 188 type 2 diabetic patients with confirmed microalbuminuria. Proteomic analysis was undertaken using capillary electrophoresis coupled to mass spectrometry to determine CKD273 classifier score. 155 samples were suitable for analysis after quality control. A previously defined CKD273 threshold of 0.343 for identification of DN was used to categorise the cohort in Kaplan-Meier and Cox regression models with all-cause mortality as the primary endpoint. Outcomes were traced through national health registers after 4 years. Results: Participants had elevated urine albumin excretion (UAE; median [IQR], 97 [40–214] mg/24 h) with preserved eGFR (mean ± SD, 88 ± 17 ml/min/1.73m 2 ). Median diabetes duration was 13 [7–19] years. The majority of patients were obese (body mass index 31.6 [28.6–35.5] kg/m 2 whereas blood pressure (129 ± 16 / 74 ± 11 mmHg) and HbA1c (58 [52–74] mmol/mol) were well controlled. There were 20 deaths during follow up of which 5 and 15 respectively occurred in the CKD273 groups below and above the threshold. Higher CKD273 score was associated with higher mortality in Kaplan-Meier analysis (Log Rank [Mantel Cox], p = 0.004). The relationship retained significance (hazard ratio 2.9 [95% CI 1.0–8.1) after adjustment for age, gender and smoking; and in a comprehensive model adjusted for age, gender, BMI, smoking status, HbA1c and blood pressure (hazard ratio 3.4 [95% CI 1.1–10.4]) where it was independent of renal parameters (p = 0.459 for eGFR; p = 0.276 for UAE). Figure. No caption available. Conclusions: The CKD273 urinary proteomic classifier predicts mortality in type 2 diabetic patients with early established kidney disease independent of markers of renal function and damage. Its performance as an early predictor of DN in normoalbuminuric diabetic patients is currently being evaluated in a prospective study (www.eu-priority.org ) where mortality will be considered as a secondary endpoint.